Pengaruh Model Pembelajaran Discovery Learning Berbantuan Geoboard Terhadap Kemampuan Pemecahan Masalah Siswa Kelas IV SD Negeri Gondoriyo - Naimah Mufafidah; Lisa Virdinarti Putra (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2023)
This study aims to determine the effect of the geoboard-assisted discovery learning model on problem-solving abilities. This type of research is an experiment with nonequivalent control group design. The population in this study were all students of Gondoriyo State Elementary School, then the research sample was class IVA and IVB of Negeri Gondoriyo Elementary School. Data collection techniques consisted of a pretest and posttest while non-technique tests consisted of observation, questionnaires, and documentation. Data analysis techniques with normality test, homogeneity test, simple linear regression test, and independent sample t-test. The result showed that there was an effect of using the geoboard-assisted discovery learning model on problem-solving abilities, evidenced by a significance level of 0,022 < 0,05 using the test simple linear regression.